Phylogeny of the weevil genus Megalostylus (Coleoptera: Curculionidae: Entiminae), endemic to Mexico - Ma Ventura Rosas-Echeverría; Alejandro Lizama-Hernández; M. Guadalupe del Rio (Revista Mexicana de Biodiversidad)
The first phylogenetic analysis of the weevil genus Megalostylus endemic to Mexico (Entiminae, Naupactini) is presented, based on a data matrix of 37 morphological characters of adults and 21 terminal taxa. The ingroup comprises 9 species, 4 varieties, and 5 specimens of Megalostylus whose identification at the species level is doubtful. The outgroup includes species representing closely related genera: Pantomorus albosignatus, Naupactus cervinus, and Megalostylodes hirsutus. The objectives were to test the monophyly of Megalostylus, to explore its species relationships, and to determine which synapomorphies allow its identification and differentiation from other genera. The analysis yielded a single cladogram of 61 steps, showing the following phylogenetic sequence: (Pantomorus albosignatus (Naupactus cervinus (Megalostylodes hirsutus (Megalostylus rhodopus (M. morpho 2 (M. macrophthalmus (M. tomentosus (M. dilaticollis (M. albicans (M. brevipilis, M. fusiformis (M. splendidus - M. sturmi))))))))))). The results support the monophyly of Megalostylus based on the following synapomorphies: protibia with a prominence opposite to mucro, elytra almost flat, sternite VIII subrhomboidal very elongated, and aedeagus smooth. They also support its sister-group relationship with Megalostylodes.